PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPAS SISWA KELAS IV SD NEGERI 28 LUBUKLINGGAU - Senjarianty, Vieonalia; Trisnayanti, Yetty; Aswarliansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the mastery of science and social learning (IPAS) outcomes of fourth-grade students at SD Negeri 28 Lubuklinggau after the implementation of the Snowball Throwing learning model. This study employed an experimental method using a One Group Pretest-Posttest Design. The sample consisted of 18 fourth-grade students of SD Negeri 28 Lubuklinggau selected using the saturated sampling technique. Data were collected through tests, and the research instrument was a multiple-choice achievement test consisting of 17 valid items. The data were analyzed using the Z-test at a significance level of α = 0.05. The results showed that the students' mean posttest score was 85.67, with a learning mastery percentage of 100%. The hypothesis testing indicated that the calculated Z value (Zcount = 6.55) was higher than the critical Z value (Ztable = 1.64); therefore, Ha was accepted and H₀ was rejected. It can be concluded that the learning outcomes of fourth-grade students at SD Negeri 28 Lubuklinggau after the implementation of the Snowball Throwing learning model achieved significant mastery